PENGARUH PENGUNGKAPAN CORPORATE SOCIAL RESPON SIBILITY,GOOD CORPORATE GOVERNANCE TERHADAP HARGA SAHAM: STUDI EMPIRIS PADA PERUSAHAAN PERTAMBANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2016 –2018 (STIE Rajawali Purworejo, 2024)
This study aims to determine the effect of Corporate Social Responsibility (CSR) and Good Corporate Governance (GCG) disclosure in stock prices. The population in this study are mining companies listed on the Indonesian Stock Exchange in 2016-2018. With purposive sampling method obtained 17 companies. The data collection used is a documentation study method by obtaining data in the form of company annual report. Proxied CSR includes CSR-Eonomy, CSR-Environment, and CSR-Social. GCG is proxied by an Independent Commissioner and an Independent Audit Committee. The data analysis technique used multiple linear regression analysis. This includes the classical assumption test, t test, coefficient determination and F test. The results show that CSR-Economic disclosure has a positive but significant effect on stock price. CSR-Environmental disclosure has a significant positive effect on stock price. CSR-Social disclosure has a significant positive effect on stock price. Each Independent Commissioner and Independent Audit Committee have a positive significant effect on stock price.